Characterization and grading of Black Bengal goat skin based on coat color - AKM Baharul Islam Talukder; Fouzia Akhter; Sanjit Chandra Barman (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
The research was conducted to study physical parameters and histological structural patterns based on the coat color of Black Bengal goat skins. Five hundred skins were randomly selected, and measured using scientific instruments and the Haematoxylin-Eosin staining method was used for histological study. Black coat color skin was found the highest (58%), the mean weight, length, and width of Black Bengal goat skin was 998.80 gm, 29.24, and 20.91 cm, respectively but there were no significant differences among the groups. The mean thickness of the skin was 1.97, 1.43, and 1.96 mm in the butt, bell, and shoulder regions, respectively, and significantly different between the groups in all categories. All slaughtered goats were flayed using the "Muchki" (Hoisting and fisting) method. The average flay cut length, depth, and mechanical and parasitic damages were 20.2 mm, 1.50 mm, 6.11, and 1.50 %, respectively. No significant difference (p > 0.05) was found in inedible fleshing by-products, but significant differences (p < 0.05) were found in trimming by-products production and salt required for curing. Salted skins were preserved for an average of 3.5 days. Hair follicles, sebaceous glands, erector pili muscles, collagen fibers, and fiber bundles were more regular in the butt region than shoulder and belly regions in the black, brown, white, and mixed coat color of Black Bengal goat skins.